Eosinophil transendothelial migration induced by the bronchoalveolar lavage fluid of acute eosinophilic pneumonia - Nakagome, Kazuyuki; Shoda, Hisakazu; Shirai, Tetsu; Nishihara, Fuyumi; Soma, Tomoyuki; Uchida, Yoshitaka; Sakamoto, Yoshio; Nagata, Makoto (Respirology (Carlton, Vic.), 2017)
ABSTRACT Background and objective Acute eosinophilic pneumonia (AEP) is characterized by a massive pulmonary infiltration of eosinophils. Mechanisms regulating the selective accumulation of eosinophils in AEP have not been fully established. The objective of this study was to evaluate the mechanisms of eosinophil accumulation in alveolar spaces through examination of bronchoalveolar lavage fluid (BALF) from AEP patients (AEP‐BALF). Methods Eosinophils were isolated from the blood of healthy subjects and were placed on a human pulmonary microvascular endothelial cell monolayer cultured on Transwell filters (Coster, Cambridge, MA, USA). A saline control solution or BALF from patients with AEP, sarcoidosis or hypersensitivity pneumonitis was applied to the lower compartment, and the transendothelial migration of the eosinophils was evaluated. The concentrations of cytokines and chemokines in BALF were also measured. Results Transmigration of eosinophils across endothelial cells was only induced by the AEP‐BALF. This transmigration was blocked by anti‐β2 integrin mAb. The concentrations of eotaxin‐2 and monocyte chemotactic protein (MCP)‐4, which are CC chemokine receptor (CCR) 3 ligands, were elevated in the AEP‐BALF, and anti‐CCR3 mAb or anti‐MCP‐4 mAb inhibited the AEP‐BALF‐induced transmigration of eosinophils. Furthermore, the concentration of leukotriene (LT) B4 was increased in the AEP‐BALF, and an LTB4 receptor antagonist partially suppressed the AEP‐BALF‐induced transmigration of eosinophils. Conclusion These findings suggest that CCR3 ligands including eotaxin‐2 and MCP‐4, and LTB4 play a role in the accumulation of eosinophils in AEP. Bronchoalveolar lavage fluid (BALF) from patients with acute eosinophilic pneumonia (AEP) induces eosinophil transendothelial migration. CC chemokine receptor (CCR) 3 ligands including eotaxin‐2 and monocyte chemotactic protein (MCP)‐4, and LTB4 may play roles in the accumulation of eosinophils in AEP.